The Impact of Unhealthy Friendships (Toxic Friendships) on the Psychological Well-Being of University Students - Lutfiah Nurani Awaliyah; Ane Sahara; Muhammad Azriel Pratama; Ati Kusmawati (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2025)
The purpose of this study was to investigate how toxic friendships affect college students’ mental health. Data were collected through in-depth interviews with a student who experienced a toxic friendship using qualitative case study methodology. The researcher demonstrated the detrimental effects of toxic friendships on college students’ mental health, including social isolation, stress, anxiety, and low self-esteem. Motivation to study and academic focus are also affected by manipulative, critical, and emotionally dominant relationships. Clients try to use coping mechanisms to deal with this situation, but emotional attachment prevents them from doing so. The results of this study show the important role played by the campus in offering psychological care to students through support groups and psychoeducation programs.